Edukasi Gizi Seimbang pada Siswa SMA Swasta Alwashliyah 1 Kota Medan - Rukmana, Erni; Yatty Destani Sandy; Kanaya Yori Damanik; Nindya Ayu Pristanti; Muhammad Edwin Fransiari (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2024)
The importance of knowledge about balanced nutrition is increasing among adolescents, because adolescence is a critical phase for forming a healthy diet that will later have an impact on long-term health. However, the low understanding of the principles of balanced nutrition guidelines is still a challenge among adolescents. This community service activity aims to improve knowledge of balanced nutrition among adolescents at Alwashliyah 1 Private High School, Medan City. The method used is lectures and discussions, involving 30 adolescents at Alwashliyah 1 Private High School, Medan City, carried out in June-July 2024. The stages of the activity include preparation, implementation, and evaluation. Data were analyzed descriptively to see age and gender and tested using a paired t-test to assess differences in knowledge before and after nutrition education. The results showed a significant increase in knowledge of balanced nutrition after the intervention (p <0.05). The conclusion of this community service activity shows that balanced nutrition education through lecture and discussion methods is effective in improving adolescent knowledge about balanced nutrition. Pentingnya pengetahuan tentang gizi seimbang semakin meningkat di kalangan remaja, karena masa remaja merupakan fase kritis untuk membentuk pola makan sehat yang nantinya berdampak pada kesehatan jangka panjang. Namun, rendahnya pemahaman tentang prinsip pedoman gizi seimbang masih menjadi tantangan di kalangan remaja. Kegiatan pengabdian ini bertujuan untuk meningkatkan pengetahuan gizi seimbang pada remaja di SMA Swasta Alwashliyah 1 Kota Medan. Metode yang digunakan adalah ceramah dan diskusi, melibatkan 30 remaja di SMA Swasta Alwashliyah 1 Kota Medan, dilaksanakan pada bulan Juni-Juli 2024. Tahapan kegiatan meliputi persiapan, pelaksanaan, dan evaluasi. Data dianalisis secara deskriptif untuk melihat usia dan jenis kelamin dan diuji menggunakan paired t-test untuk menilai perbedaan pengetahuan sebelum dan sesudah pendidikan gizi. Hasil menunjukkan peningkatan yang signifikan pada pengetahuan gizi seimbang setelah intervensi (p<0,05). Kesimpulan dari kegiatan pengabdian ini menunjukkan bahwa pendidikan gizi seimbang melalui metode ceramah dan diskusi efektif dalam meningkatkan pengetahuan remaja mengenai gizi seimbang.